Pengembangan Kurikulum PAI Berbasis Kecerdasan Artificial Intelligence dalam Pembelajaran Modern - Suci Kurnia, Syifa Al Ghefira, Zakiah Zahran Febridirani, Abdurrahmansyah (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2026)
The rapid development of digital technology, especially artificial intelligence (AI), has caused academic anxiety related to the readiness of the Islamic Religious Education (PAI) curriculum in facing the demands of modern learning. The PAI curriculum is required not only to be able to integrate technology, but also to maintain the spiritual values and character of students. This research aims to examine the development of AI-based PAI curriculum in modern learning. The method used is a qualitative approach with the type of library research through the analysis of various relevant literature. The results show that AI has an important role in creating adaptive, interactive, and personalized learning, so that it can increase the effectiveness of PAI learning. The concept of the modern PAI curriculum emphasizes a balance between cognitive, affective, and spiritual aspects. However, its implementation faces challenges in the form of limited educator competencies, infrastructure, and the potential for reduced affective values. Nonetheless, AI also provides a great opportunity in creating more relevant and contextual learning. In conclusion, the development of an AI-based PAI curriculum needs to be carried out wisely and in a targeted manner in order to be able to make an optimal contribution to the development of Islamic education in the modern era.